1957
DOI: 10.1590/s0004-282x1957000200001
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição do contraste em angiografias cerebrais: I - Angiografias carotídeas com enchimento do tronco basilar

Abstract: O afluxo de sangue arterial para o encéfalo é feito através das duas carótidas internas e das duas artérias vertebrais. Estas, fundindo-se ao nível do sulco bulbo-protuberancial, dão origem ao tronco basilar. Pouco antes de sua fusão, cada uma das artérias vertebrais emite um ramo -artéria cerebelosa póstero-inferior -o qual irriga território restrito do rombencé-falo; não sendo levado em conta esse pequeno território de distribuição das artérias cerebelosas póstero-inferiores e fazendo abstração das anastomos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1957
1957
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The importance of this artery as the origin of collateral circulation to the brain has already been emphasized. [13][14][15] AbuRhama et al (1998), when studying the natural history of total occlusion of the bilateral internal carotid in a group of patients, showed that after surgical brain revascularization patients presented long-term mortality and stroke rates that were lower than for those treated conservatively. Most of them had their blood flow restored through the external carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this artery as the origin of collateral circulation to the brain has already been emphasized. [13][14][15] AbuRhama et al (1998), when studying the natural history of total occlusion of the bilateral internal carotid in a group of patients, showed that after surgical brain revascularization patients presented long-term mortality and stroke rates that were lower than for those treated conservatively. Most of them had their blood flow restored through the external carotid artery.…”
Section: Discussionmentioning
confidence: 99%